Ricardo Piglia, una poética de la reescritura - Romero, Julia Graciela (Centro de Estudios de Teoría y Crítica Literaria, IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. UNLP, 2009)
This article constitutes a first approach to the manuscripts of Prisión perpetua, the consideration of a future archive and the theoretical and critical reflections that such an event arouses. We also advance the figuration of a poetics based on the mechanism of rewriting, and especially of a type of rewriting that we here call 'Menard's strategy', whereby the recontextualizations of the own work conform a system of narrative profitability which results in the multiplication on the level of textual production